In vitro antimicrobial effects and mechanism of atmospheric-pressure He/O2 plasma jet on Staphylococcus aureus biofilm. (9th February 2017) - Xu, Zimu; Shen, Jie; Cheng, Cheng; Hu, Shuheng; Lan, Yan; Chu, Paul K
Abstract: The antimicrobial effects and associated mechanism of inactivation of Staphylococcus aureus ( S. aureus ) NCTC-8325 biofilms induced by a He/O2 atmospheric-pressure plasma jet (APPJ) are investigated in vitro . According to CFU (colony forming units) counting and the resazurin-based assay, the 10 min He/O2 (0.5%) APPJ treatment produces the optimal inactivation efficacy (>5 log10 ml −1 ) against the S. aureus biofilm and 5% of the bacteria enter a viable but non-culturable (VBNC) state. Meanwhile, 94% of the bacteria suffer from membrane damage according to SYTO 9/PI counterstaining. Scanning electron microscopy (SEM) reveals that plasma exposure erodes the extracellular polymeric substances (EPS) and then the cellular structure. The H2 DCFDA-stained biofilms show larger concentrations of intracellular reactive oxygen species (ROS) in membrane-intact bacteria with increasing plasma dose. The admixture of oxygen in the working gas highly contributes to the deactivation efficacy of the APPJ against S. aureus and the plasma-induced endogenous ROS may work together with the discharge-generated ROS to continuously damage the bacterial membrane structure leading to deactivation of the biofilm microbes.